Measuring the Causes of Saudi Arabian Construction Accidents: Management and Concerns - Moosa, Majed M; Oriet, Leo P.; Khamaj, Abdulrahman M (International Journal of Occupational Safety and Health, 2020)
Introduction: Research indicate that construction site accidents are a global concern, and rates are rapidly increasing. In developing countries such as Saudi Arabia, safety issues are frequently ignored, and little is known about their causes. Objectives: This study aimed to shed light on factors causing accidents in Saudi Arabian construction companies. Methods: An online detailed survey, using Google Form, of accident features was distributed randomly to potential employees in 35 construction companies in Saudi Arabia, where one of the top administrators or safety officers were required to respond to the survey. It was conducted from 1st June to 31st August, 2013. The safety practices and perceptions of accident causes were assessed. Results: The response rate was 63%. Over half of the surveyed organizations encountered all of the selected accident types. While 19 (86%) of the construction companies maintained the equipment regularly, 15 (68%) had regular maintenance staff and 13 (59%) inspected the equipment before use. Although 18 (82%) of the workers were supplied with personal protective equipment (PPE), only 12 (55%) emphasized its use and offered site orientation for new employees. In the last part of the survey, respondents were requested to rate 25 factors affecting safety performance at the construction sites on a scale of 1 to 5, with 5 being the most important. The three most important factors of poor safety performance were the firm's top leaders, a lack of training, and the reckless operation of equipment. Conclusion: Changing attitudes of surrounding safety culture have the potential to significantly improve safety outcomes in the Saudi Arabian construction industry. Two Saudi Arabian corporations, Saudi Aramco and Saudi Chevron Petrochemical provide a positive model for increasing construction safety in the country, but there is a paucity of industry-level data. Further scholarly attention is strongly indicated.